Gender as a moderator of the relationship between life stress and psychopathology. - Fu, Karen Jianing. (2009)
This study examined the relationship between cumulative stressful life events and internalizing, externalizing, and total problem behaviors in children and adolescents. One thousand cases assessed in the year 2007 at the Child Guidance Clinic were randomly sampled. An increase in the total number of stressful life events was positively associated with increased Child Behavioral Checklist (CBCL) externalizing, internalizing, and total problem scores. Boys scored higher than girls on the externalizing and total problem scales, while both genders scored similarly on the internalizing problem scale. Gender moderated the relationship between life events and externalizing problems, but not the relationship between life events and internalizing problems. These findings have implications for prevention and intervention efforts that attempt to address problem behaviors in children/adolescents.